1987
DOI: 10.1017/s0022216x0001717x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Class on Activity Preferences of Comunidades Eclesiais de Base (CEBs) in the Archdiocese of São Paulo

Abstract: A number of interpretations have recently emerged which attempt to explain the nature and sociopolitical implications of Roman Catholic base Christian communities (CEBs) in Brazil. Most studies have tended to describe these small, informal lay groups as a predominantly lower-class phenomenon which is facilitating the self-liberation of the poor from the weight of centuries-old political and economic oppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The 1988 research also suggests that levels of intragroup heterogeneity and conflict, noted in previous studies to be hampering CEB effectiveness in the political sphere (see Hewitt, 1986), are diminishing. This becomes apparent if we examine changes in group members' attitudes and behavior over the previous four years within those more advanced groups specifically involved in the revindicaq&s. These numbered six in 1984, and eight in 1988.…”
Section: Recent Tendencies In Ceb Activation In the Political Spherementioning
confidence: 88%
See 4 more Smart Citations
“…The 1988 research also suggests that levels of intragroup heterogeneity and conflict, noted in previous studies to be hampering CEB effectiveness in the political sphere (see Hewitt, 1986), are diminishing. This becomes apparent if we examine changes in group members' attitudes and behavior over the previous four years within those more advanced groups specifically involved in the revindicaq&s. These numbered six in 1984, and eight in 1988.…”
Section: Recent Tendencies In Ceb Activation In the Political Spherementioning
confidence: 88%
“…One study conducted after the 1982 general elections in Brazil (see Hewitt, 1983) showed no correlation between areas of CEB concentration and the election of PT members to federal or state legislatures. In the city of Rio de Janeiro, for example, PT members running in more affluent areas were justas likely to be elected as those in less affluent ones with much higher CEB concentrations.…”
Section: Religion and The Consolidation Of Democracy In Brazil 141mentioning
confidence: 99%
See 3 more Smart Citations